Does TQM support innovation performance in Malaysia’s manufacturing industry? - Ooi, Keng-Boon; Lin, Binshan; Teh, Pei-Lee; Chong, Alain Yee-Loong (Journal of Business Economics and Management, 2012)
This empirical study examines the association of TQM practices (i.e. leadership, customer focus, strategic planning, people management, information analysis and process management) with the innovation performance as perceived by the managers in Malaysia. The research model is constructed on the basis of established theory and on well-known criteria such as Malcolm Baldrige National Quality Award. Six hypotheses are formulated and tested by multiple regression based on a sample of 206 managers working in the ISO 9001:2000 certified manufacturing firms in Malaysia. The results of this study show that TQM has a significant positive relationship with innovation performance. In particular, the findings of this study show that process management, strategic planning, people management and customer focus have positive relationships with innovation performance of firms surveyed in Malaysia. Therefore, both researchers and practitioners are advised to consider these relevant TQM practices when assessing the innovation performance of an organization. Implications for managers and researchers, as well as study limitations are also discussed.